Table Tennis Forehand Drive Learning Model for Application based Elementary School Students - Agus Kurniadi; Hernawan Hernawan; Sri Nuraini (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research produces a learning model for table tennis forehand drive strokes for upper elementary school students and tests the effectiveness of an application-based table tennis forehand stroke skill model for upper elementary school students. The research approach and method for this table tennis Forehand drive stroke skill learning model uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) research and development model. The subjects involved in this research were 34. The subjects of this research were upper elementary school students. The data analysis technique was created by conducting a pretest and posttest using a forehand drive stroke skill movement instrument. The results are analyzed, the point is to find out whether there is a percentage increase in skills through the learning model given to students. Based on the results of the analysis, it was found that there was an increase in the ability of table tennis forehand drive strokes for elementary school IV students after implementing the forehand drive movement learning model. The results obtained were 6.41% pre-test and 8.65% post-test.